The Role of China in the International Balance of Power After the Russian Invasion of Ukraine - Ahmed, Ahmed Abdulkarim (Journal of Legal and Political Studies, 2024)
China's policy towards the Russian-Ukrainian war is characterized by ambiguity, as it balances its strong relations with Russia and its interests with the West. China seeks to reduce American hegemony and support a multipolar world order through alliances such as BRICS and the Shanghai Cooperation Organization. China employs tools like the Belt and Road Initiative and the digital economy to enhance its influence. Through the Russian-Ukrainian war, China is also testing Western reactions to any potential Chinese intervention in Taiwan. This war presents an opportunity for China to present itself as a rising power capable of reshaping the international power balance towards multipolarity, rather than unipolarity. Keywords: Chinese Soft Power, Multipolarity, Belt and Road Initiative, Chinese Digital Economy, Chinese Strategies After the War.
Keywords: Chinese Soft Power; Multipolarity; Belt and Road Initiative; Chinese Digital Economy; Chinese Strategies After the War